Solitary fibrous tumor/hemangiopericytoma in the cerebellopontine angle mimicking vestibular schwannoma: A case report and literature review. Issue 13 (March 2020) - Yue, Xi; Huang, Jie; Zhu, Yaqi; Du, Yong
Abstract: Rationale: Intracranial solitary fibrous tumors (SFTs) and hemangiopericytomas (HPCs) are rare spindle cell tumors of mesenchymal origin that include benign and malignant neoplasms. Patient concerns: We present a 66-year-old male with a 5-year history of headache and dizziness, with left progressive sensorineural hearing loss over 1 month. Diagnoses: WHO grade II SFT/HPC originating from the internal auditory canal in the left cerebellopontine angle. Interventions: surgical resection. Outcomes: No local recurrence or metastases were observed in the follow-up 3 months after the surgery. Lessons: Intracranial SFTs/HPCs are rare mesenchymal neoplasms that are challenging to manage. If the imaging characteristics of tumor are not typical, clinicians should depend on tissue biopsy and immunohistochemistry to make a definitive diagnosis.